If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 1(3x + 2) = 17 Reorder the terms: 2x + 1(2 + 3x) = 17 2x + (2 * 1 + 3x * 1) = 17 2x + (2 + 3x) = 17 Reorder the terms: 2 + 2x + 3x = 17 Combine like terms: 2x + 3x = 5x 2 + 5x = 17 Solving 2 + 5x = 17 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 5x = 17 + -2 Combine like terms: 2 + -2 = 0 0 + 5x = 17 + -2 5x = 17 + -2 Combine like terms: 17 + -2 = 15 5x = 15 Divide each side by '5'. x = 3 Simplifying x = 3
| -x+6y=25 | | z*6=24 | | (2w-2)(w-2)=32 | | z*6= | | x+9y=50 | | 12x+2y=47.90 | | -2(-2y+7)+3y=14 | | (2z+3)(2-z)=0 | | 72=v+8v | | (6m-2/5n)^2 | | 6x-5(3x-10)=14 | | log(x)+log(x-3)=log(28) | | 3(x+2)=2(2x+7) | | 6=15u-9u | | X+24=43.5 | | 4x+6y+3=17 | | 4x-7(x+3)=-36 | | 2.53-x=6.8 | | a-3=2.45 | | 16p/7=(2p-7)/4 | | y-4=-2/3 | | -12/x=3/4 | | 2x+33=3+7x-5 | | 9x-4=2x+12 | | 6y*y/6y | | B^2+4b=8 | | 6t^2+24t-100=0 | | 3x^3+4x^2+8x+6= | | 6x+6y=31.78 | | X^2+2x-99999=0 | | 6x+6y=31.95 | | X/5=36/4 |